Innovation and Hygiene Improvement Training with Content Creators and MSMEs in Improving the Culinary Industry in Indonesia : Penelitian - I Wayan Suadnyana; Febianti; Putu Herny Susanti; Gede Eka Wahyu; Firlie Lanovia Amir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article collaborates with several Balinese influencers to improve innovation capabilities and several academics in the health field to improve hygiene in culinary UMKM in Bali. This conclusion in tis article show The improvement of innovation capabilities that the author socialized was around creating content to increase marketing reach. The ideas for culinary content for MSMEs that the author socialized include the following: 1. Customer Reviews. 2. Cooking Preparation Demo. 3. Behind the Scenes. 4. Introducing employees in the kitchen or admin.5. Re-share customer posts: Generally, if your customers see that their posts are re-shared on your culinary business account, they will be happy. Thus, you have also opened up opportunities for other customers to also buy products from your storefront. In addition to the 5 ideas above that you can do to attract a lot of attention from customers, you can also do a live streaming session which is also useful for increasing closeness with customers. The author socialized these five ideas with the aim of developing his business so that it can develop further and even penetrate the national market. Not only developing innovation capabilities by creating interesting content, the author also socializes about food hygiene. Some principles of food hygiene and sanitation include the following: 1. Personal Hygiene 2. Environmental Hygiene. 3. Safety of Raw Materials. 4. Proper Handling and Storage. 5. Hygiene Training and Certification. Thus, food quality and safety can be guaranteed properly.The socialization carried out by the author regarding the development of innovation capabilities by creating creative content around culinary and improving food hygiene and sanitation is carried out with the hope that MSMEs in Bali can continue to develop and even penetrate the national market and be able to create a healthy Bali because of healthy food.